Enforcement Of The Ban On Probationary Periods In Fixed-Time Work Agreements (Pkwt) The Role Of The Batam City Manpower Supervision Upt - Leny Besouw; David Tan (PALAR | PAKUAN LAW REVIEW, 2026)
This study aims to analyze the role of the Batam City Manpower Supervision Unit in supervising the prohibition of probationary periods in the Fixed-Time Work Agreement (PKWT), the obstacles faced, and the efforts made in enforcing labor norms. The prohibition of probationary periods in PKWT has been regulated in Law Number 13 of 2003 as amended through Law Number 6 of 2023 concerning Job Creation and Government Regulation Number 35 of 2021. However, in practice, companies are still found that apply a trial period with other terms that have the potential to harm workers.This study uses an empirical juridical method with a qualitative approach. Data were obtained through interviews, literature studies, and analysis of laws and regulations. The results of the study show that the Batam City Manpower Supervision Unit has carried out supervision through the stages of planning, inspection, and reporting in accordance with the provisions of the Regulation of the Minister of Manpower Number 33 of 2016. However, the implementation of supervision has not been optimal due to the limited number of supervisors, facilities and infrastructure, the weak implementation of administrative sanctions, low legal awareness, and a work culture that still tolerates probationary periods in PKWT. Therefore, it is necessary to strengthen supervision, improve operational facilities, add labor supervisors, and socialize the law in an ongoing manner to increase legal protection for PKWT workers in Batam City.   Keywords: PKWT, probation, labor supervision, law enforcement, legal protection.